INTENTIONAL HOMICIDE IN THE STATE OF GUANAJUATO: AN INTERSYSTEMIC CRIMINOLOGICAL STUDY AND MULTIFACTORIAL INTERACTION - Valenzuela Viramontes, Omar (2025)
The rising incidence of intentional homicide in Guanajuato and its unidimensional analysis have limited a comprehensive understanding of the phenomenon. This mixed-method study examined individuals incarcerated between 2019 and 2021 for intentional homicide and the perceptions of social sectors in Guanajuato. Using a diverse theoretical framework, including the adaptation of Human Development Ecological Theory, 134 multidimensional factors were identified, with expressive circumstances and problematic substance use as key influences. The study highlights the value of combining qualitative narratives from incarcerated individuals with quantitative approaches to design more effective policies.